The SAGE handbook of international social work - Hall, Nigel; Hokenstad, Merl C.; Pawar, Manohar S.; Lyons, Karen 1944-; Huegler, Nathalie (SAGE Publications, 2012)
Contributions tackle both the global and local aspect of social work in its various forms and interrogate the key concerns that societies are facing through an international lens. The contributors show that, with an appreciation of commonalities and differences, local practices and appropriate forms of international activity can be better developed.